2023
DOI: 10.3389/fsurg.2023.1280383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, management and outcomes of bile duct injuries after laparoscopic cholecystectomy: a 15-year single-center experience in Vietnam

Hung Quang Vu,
Duc Trong Quach,
Bac Hoang Nguyen
et al.

Abstract: ObjectivesTo evaluate the clinical presentation, management, and outcomes of bile duct injuries (BDIs) after laparoscopic cholecystectomy (LC).MethodsThis is a case series of 28 patients with BDIs after LC treated at a tertiary hospital in Vietnam during the 2006-2021 period. The BDI's clinical presentations, Strasberg classification types, management methods, and outcomes were reported.ResultsBDIs were diagnosed intraoperatively in 3 (10.7%) patients and postoperatively in 25 (89.3%). The BDI types included S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Clinical manifestations and laboratories are non-specific, and the diagnosis requires high suspicion. In this investigation, it was observed that 15% of patients received an intraoperative diagnosis akin to the findings reported by Vu et al albeit lower than the estimates reported in the literature, where it is suggested that approximately one-third of patients with Strasberg A-D lesions, and up to 70-80% of patients with Strasberg E lesions, have an intraoperative diagnosis [ 6 , 8 , 17 ].…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Clinical manifestations and laboratories are non-specific, and the diagnosis requires high suspicion. In this investigation, it was observed that 15% of patients received an intraoperative diagnosis akin to the findings reported by Vu et al albeit lower than the estimates reported in the literature, where it is suggested that approximately one-third of patients with Strasberg A-D lesions, and up to 70-80% of patients with Strasberg E lesions, have an intraoperative diagnosis [ 6 , 8 , 17 ].…”
Section: Discussionmentioning
confidence: 48%
“…Although Strasberg type A lesion is the most common post-cholecystectomy form [ 6 , 27 ], in our research, the most frequent types were E2 and E4, with a percentage of 25% each. This distribution aligns with the findings of studies by Wani et al in 2019, who classified bile duct lesions with MR cholangiography in 25 patients, with types E3 (40%), E2 (36%), and E4 (12%) being the most frequent [ 28 ].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations